Viability and Stability of Lactobacillus Plantarum Mut 7 FNCC 250 Suplemented in Papaya-Pineapple Juice During Storage - Sri Hartati; Eni Harmayani; Endang S Rahayu; Tyas Utami (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2003)
Lactobacillus plantarum Mut7 FNCC 250 is an indigenous bacterium isolated from fermented food (“gatot”) and a potential agent to reduce cholesterol. Study the on aplication of the bacterium as probiotic agent to food stuff is needed. The purpose of the study was to prepare formula of papaya-pineapple juice as probiotic carrier and to study the viability and capability of Lactobacillus plantarum Mut7 FNCC 250 to assimilate cholesterol during three months storage. Fruits juice was prepared with different formula and organoleptically tested. Selected juice formula was supplemented with Lactobacillus plantarum Mut7 FNCC 250 and stored in cool room (4-5 oC). During three month storage, the value of pH the product, cell viability and ability to assimilate cholesterol were evaluated. The result indicated that acceptable formula was papaya juice added with 25 % pineapple. Viability of Lactobacillus plantarum Mut7 FNCC 250 supplemented in papaya- pineapple juice was stable (decrease of < 1 log cycle), while the pH of the juice decreased after 3 month storage. The ability of Lactobacillus plantarum Mut7 FNCC 250 to assimilate cholesterol was stable within 2 months storage, but decreased after 3 months. Key words : Viability, sta, Lactobacillus plantarum, probiotic, papaya-pineapple juice.